2010
DOI: 10.5194/acp-10-3335-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hygroscopic seeding on warm rain clouds – numerical study using a hybrid cloud microphysical model

Abstract: Abstract. The effect of hygroscopic seeding on warm rain clouds was examined using a hybrid cloud microphysical model combining a Lagrangian Cloud Condensation Nuclei (CCN) activation model, a semi-Lagrangian droplet growth model, and an Eulerian spatial model for advection and sedimentation of droplets. This hybrid cloud microphysical model accurately estimated the effects of CCN on cloud microstructure and suggested the following conclusions for a moderate continental air mass (an air mass with a large numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…For example, Kuba and Fujiyoshi (2006) and Kuba and Murakami (2010) demonstrated by using a hybrid cloud microphysical model that the effect of cloud seeding on the raindrop formation rate depends the characteristics of the background aerosol. They showed that seeding with large-particle cloud condensation nuclei (CCN) increases the amount of rainfall under polluted conditions (i.e., when there is a large number concentration of small hygroscopic particles), whereas it decreases the amount of rainfall under unpolluted conditions (i.e., a small number concentration of small hygroscopic particles).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kuba and Fujiyoshi (2006) and Kuba and Murakami (2010) demonstrated by using a hybrid cloud microphysical model that the effect of cloud seeding on the raindrop formation rate depends the characteristics of the background aerosol. They showed that seeding with large-particle cloud condensation nuclei (CCN) increases the amount of rainfall under polluted conditions (i.e., when there is a large number concentration of small hygroscopic particles), whereas it decreases the amount of rainfall under unpolluted conditions (i.e., a small number concentration of small hygroscopic particles).…”
Section: Introductionmentioning
confidence: 99%
“…The model used in this study is a hybrid microphysical cloud model with a two‐moment bin method [ Kuba and Fujiyoshi , ; Kuba and Murakami , ] that was developed to estimate the number concentration and size distribution of cloud droplets accurately, along with the effect of CCN on cloud microstructures. The activation of CCN and the initial condensational growth were computed in a Lagrangian particle framework using a parcel model.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the non-hydrostatic icosahedral atmospheric model (NICAM; e.g., Tomita and Satoh, 2004;Satoh et al, 2008) has made it possible to reproduce cloud-related phenomena with a horizontal resolution of less than 1 km (Miyamoto et al, 2013). Furthermore, a hybrid microphysical cloud model with a two-moment bin method (Kuba and Fujiyoshi, 2006;Kuba and Murakami, 2010) has been developed; therefore, the understanding of the smaller-scale phenomena is crucially necessary. Incorporating the results of this study into these models would greatly improve the accuracy of model simulations through motivating better representations of the rainfall parameterization and physically based process description.…”
Section: Discussionmentioning
confidence: 99%